1988
DOI: 10.1111/j.1365-246x.1988.tb01391.x
|View full text |Cite
|
Sign up to set email alerts
|

Carboniferous palaeomagnetic investigations in Morocco: Permian remagnetizations and possible large Carboniferous rotations occurring in Mesetian sedimentary and Jebilets intrusive rocks

Abstract: Carboniferous limestone and sandstone formations from the Moroccan Meseta and Visean gabbros from the Jebilets massif have been investigated. Palaeomagnetic results reveal the occurrence of different magnetic components. These are (i) a Permian component: Dm = 141.5", Zm = -1.7", N = 4 [Virtual Geomagnetic Pole (VGP) = 33"S, 43.9"E], similar to that found in the Anti-Atlas and in other parts of the Hercynian chain, (ii) a Carboniferous component Dm = 116.6", Zm = 25. lo, N = 9 (VGP = 7.4"S, 54.5"E), consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…These directions correspond to that of the Permian overprint already observed in other studies in Africa (e.g. Daly & Irving 1983; Salmon et al 1988; Aïfa 1993). In the Lower Stephano‐Autunian Formation (sample TG18A on Fig.…”
Section: Palaeomagnetic Analysissupporting
confidence: 89%
“…These directions correspond to that of the Permian overprint already observed in other studies in Africa (e.g. Daly & Irving 1983; Salmon et al 1988; Aïfa 1993). In the Lower Stephano‐Autunian Formation (sample TG18A on Fig.…”
Section: Palaeomagnetic Analysissupporting
confidence: 89%
“…This signature strongly contrasts with the late Paleozoic remagnetization seen elsewhere in the Great Basin, as the remagnetization resides in magnetite in all other known cases. Jackson et al [1993] suggested that pyrrhotite, in association with magnetite, may be important in imparting the distinctive rock magnetic properties seen in many ancient remagnetized carbonate rocks, and Salmon et al [1988a, 1988b] have also reported pyrrhotite carrying a Permian signature in remagnetized middle Paleozoic miogeoclinal rocks in Morocco. Indeed, as the magnetite in ancient carbonate rocks is commonly of late diagenetic origin [ McCabe and Elmore , 1989], formation of pyrrhotite at the expense of magnetite may help account for the common lack of primary magnetite capable of recording a stable paleomagnetic signature in such rocks.…”
Section: Discussionmentioning
confidence: 99%